High‐Resolution Capillary Printing of Eutectic Gallium Alloys for Printed Electronics. Issue 11 (17th July 2021) - Hussain, Navid; Fu, Tongtong; Marques, Gabriel; Das, Chittaranjan; Scherer, Torsten; Bog, Uwe; Berner, Lukas; Wacker, Irene; Schröder, Rasmus R.; Aghassi‐Hagmann, Jasmin; Hirtz, Michael
Abstract: A versatile liquid metal (LM) printing process enabling the fabrication of various fully printed devices such as intra‐ and interconnect wires, resistors, diodes, transistors, and basic circuit elements such as inverters which are process compatible with other digital printing and thin film structuring methods for integration is presented. For this, a glass capillary‐based direct‐write method for printing LMs such as eutectic gallium alloys, exploring the potential for fully printed LM‐enabled devices is demonstrated. Examples for successful device fabrication include resistors, p–n diodes, and field effect transistors. The device functionality and easiness of one integrated fabrication flow shows that the potential of LM printing is far exceeding the use of interconnecting conventional electronic devices in printed electronics. Abstract : Direct writing of liquid metal (LM) via capillary printing is applied for printed electronic microdevices, exemplified by resistors, p–n diodes and field effect transistors. These examples and the demonstrated fabrication workflow show that the potential for LM printing in printed electronics is far exceeding the use as flexible interconnect of conventional electronic devices.